Coincidental discovery of HIV and pregnancy positive status in primary healthcare facilities - Morongwa R. Sekele; Mygirl P. Lowane; Mathildah Mokgatle (AOSIS, 2024)
Background: HIV-positive and pregnancy diagnosis is a traumatic, shocking, and distressing experience for women. Adoption of routine HIV counselling and testing in the antenatal programme aimed to increase the uptake and the early diagnosis of HIV among pregnant women to prevent maternal HIV transmission to unborn babies and neonates. Objectives: The study aimed to explore the psychological reaction of women coincidentally discovering their HIV-positive status and pregnancy while seeking medical care in primary healthcare facilities in the Tshwane district. Method: Descriptive phenomenology involving a semi-structured in-depth interview was used to collect data. The sample was purposively selected. Twenty-eight women participated in the research project. Face-to-face in-depth audio recorded interviews were used to gain a full understanding of the experiences and feelings of the participants. Results: Reason for the uptake of pregnancy and HIV testing, reactions upon discovering HIV and pregnancy-positive status, emotions arising from the pregnancy and HIV-positive diagnosis, understanding HIV infection in pregnancy, and transitions to acceptance and coping with the HIV-positive diagnosis were themes that emerged from this study. Conclusion: It is crucial that responsible healthcare workers consider this psychological imbalance during their offering of antenatal and postnatal care services so that the pregnant women living with HIV can accept and cope with the situation. Contribution: This study accounts to support other studies that offer intense counselling for women coincidentally discovering their positive HIV status and pregnancy. It is important to remedy the acceptance of the situation and to promote HIV prevention and family planning for women of childbearing age.